2020
DOI: 10.1002/saj2.20116
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon sequestration when converting a rainfed cropping system to irrigated corn under different tillage systems and N fertilizer rates

Abstract: The aim of this study was to evaluate the impact of 21 years of tillage and N fertilization and the conversion from a rainfed to an irrigated cropping system on soil organic C (SOC). The study was carried out in northeastern Spain in a long‐term tillage and N rate field experiment established in 1996 under barley rainfed conditions, which in 2015 was converted into irrigation with corn. Three types of tillage (conventional tillage, CT; reduced tillage, RT; no‐tillage, NT) and three mineral N fertilization rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In semiarid Spanish conditions, a significant increase in SOC levels was observed three years after the conversion from rainfed to irrigated cropland (Pareja-Sánchez et al, 2020). In this last study, an increase in C inputs under sprinkler irrigated conditions explained more than 70 % of the variability in SOC change rates between rainfed and irrigated periods (Pareja-Sánchez et al, 2020). Similarly, in Central Great Plains (USA) greater SOC levels were observed in irrigated agroecosystems when different rainfed and irrigated fields were compared (Denef et al, 2008).…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…In semiarid Spanish conditions, a significant increase in SOC levels was observed three years after the conversion from rainfed to irrigated cropland (Pareja-Sánchez et al, 2020). In this last study, an increase in C inputs under sprinkler irrigated conditions explained more than 70 % of the variability in SOC change rates between rainfed and irrigated periods (Pareja-Sánchez et al, 2020). Similarly, in Central Great Plains (USA) greater SOC levels were observed in irrigated agroecosystems when different rainfed and irrigated fields were compared (Denef et al, 2008).…”
Section: Introductionmentioning
confidence: 60%
“…However, when comparing the POM-C, this proportion reached almost 38 %. In an experiment located under similar Mediterranean conditions, the POM-C fraction was identified as an early indicator of SOC changes when a rainfed cropping system was converted to irrigated maize (Pareja-Sánchez et al, 2020). In particular, these same authors observed increases of about 75 % in POM-C levels when rainfed systems were converted to irrigated maize systems (Pareja-Sánchez et al, 2020).…”
Section: Tablementioning
confidence: 92%
See 1 more Smart Citation
“…In this framework, irrigated agriculture, both due to its fundamental role in the food and raw material supply chain globally (23% of cultivated land representing 45% of total food production), as well as for its potential as a climate-smart soil management strategy, has received worldwide scientific interest in recent decades (Velasco-Muñoz et al, 2019). The potential of irrigated agriculture to sequester C in the soil is widely documented in the literature (Lal, 2020c;Pareja-Sánchez et al, 2020). Disparity in results is however observed, with some showing positive effects and others negative or nil Mudge et al, 2017;, where differences in climate and soil characteristics seem to play a key role .…”
Section: Irrigation Cross-sectional Analysismentioning
confidence: 99%
“…Assessing the impact of the adoption of irrigation on soil quality and functioning, and in particular on organic matter storage, seems necessary to better understand its benefits and drawbacks in terms of agricultural sustainability and climate policies. In terms of soil organic C (SOC) storage, irrigation may have positive effects in arid and semiarid areas Pareja-Sánchez et al, 2020). It is, for instance, one of the measures considered within those proposed in the "4 per 1000" initiative framework (Minasny et al, 2017), which aims to address the global challenge of securing food for a growing population, while ensuring climate change adaptation and mitigation .…”
Section: Introductionmentioning
confidence: 99%